ANALISIS PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK DI KANTOR KECAMATAN PALU BARAT KOTA PALU - Tahadju, Marthina (Katalogis, 2016)
The objectives of the study were to analyze the processing service of Electronic Identity Card at the Office of west Palu District Palu City and to determine the influencing factor. Informants in this studyÂ amounted to 7 people, consisting of 4 employees and 3 people. The technique used in informant determination was purposive sampling, namely selecting or choosing informants, interviews, and documentations, namely selecting informants deliberately. Data were collected using observations, interview and documentation techniques. The type of research used in this study was qualitative descriptive research. The theory or concept used was the theory or concept of Parasurahman in Sinambela (2006:7). The results showed that the processing Service of KTP-el at of the office of West Palu District Palu City had not been performed well, based on the five indicator used as benchmark, namely Reliability, Tangibles, Responsiveness, Assurance and Empathy, only three factor that had been met well, namely (1) The Responsiveness indicator: there were desires from the District apparatuses to provide service responsively; (2) The assurance indicator: there were friendliness and responsibilities from the District apparatuses to any people complain related to KTP-el Processing; and (3) The Empathy indicator: there were concerns and appearances from the district apparatuses faced by the people in the service provision to the people. Meanwhile, the other two indicators, namely the reliability indicator: there were still people who do not receive service as promised; and the tangibles indicators: the workroom of KTP-el processing service was inadequate so it could inhibit the process of KTP-el processing.Â Â